2007
DOI: 10.1021/cm0716598
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Study of the Role of H and Na in AB-Type Carbonate Hydroxylapatite

Abstract: Solid-state nuclear magnetic resonance (NMR) techniques, combined with Fourier transform infrared (FT-IR) spectroscopy, were used to study synthetic AB-type carbonate hydroxylapatite (CHAp). 13C{1H} heteronuclear correlation (HetCor) experiments indicate that the two carbonate environments represented by the peaks at δC = 169.8 and 170.8 ppm are associated with three H environments with one environment represented by a peak centered about δH = 0.0 ppm and two additional peaks located at 1.3 and 5.5 ppm. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 33 publications
9
72
1
Order By: Relevance
“…A chemical shift of δ H = −0.3 ppm is close to that previously assigned to hydroxyl groups in hydroxylapatite [28,51] and its relative intensity in this spectrum, about 26%, is similar to the relative phase abundance of ApPb50B determined by Reitveld analysis. This interpretation was tested using 1 H/ 207 Pb double resonance methods.…”
Section: H Mas Nmrsupporting
confidence: 85%
“…A chemical shift of δ H = −0.3 ppm is close to that previously assigned to hydroxyl groups in hydroxylapatite [28,51] and its relative intensity in this spectrum, about 26%, is similar to the relative phase abundance of ApPb50B determined by Reitveld analysis. This interpretation was tested using 1 H/ 207 Pb double resonance methods.…”
Section: H Mas Nmrsupporting
confidence: 85%
“…The presence of Na + inside the apatite phase of HB and CT is not fully surprising given that previous studies of crystalline Na-substituted calcium-phosphate phases have shown that Ca 2+ is readily replaced by Na + in phosphates, 63,98 despite the difference in charge between the two cations. Such a situation is likely to be related to the close similarity between ionic radii of Na + and Ca 2+ (1.02 Å vs. 1.00 Å ), 103 leading to similar average MÁ Á ÁO bond distances in sodium and calcium phosphates (B2.42 AE 0.70 Å for M = Na, 104 vs. B2.45 AE 0.60 Å for M = Ca).…”
Section: H{mentioning
confidence: 92%
“…51 In addition, 23 Na MRI has been used to analyse the structure of biological tissues like mummified bone and cartilage, 61,62 and it has recently been shown that the local environment of sodium in synthetic carbonated apatites can be studied by 23 Na solid state NMR. 63 In 2005, in a review on ''Solid State NMR Studies of Bone'', 24 Kolodziejski concluded that ''quadrupolar nuclei like 23 Na and…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural role of carbonate in hydroxyapatite (HAP) and fluorapatite (FAP) has been investigated extensively by X-ray powder and single-crystal and neutron powder diffraction methods [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], as well as by infrared (IR, FTIR), Raman and nuclear magnetic resonance (NMR) spectroscopy [23][24][25][26][27][28][29][30][31][32]. It has been established that the carbonate ion can be accommodated either in the c-axis structural channel or as a substituent for the phosphate group: the former carbonate is known as type A and the latter as type B.…”
Section: Introductionmentioning
confidence: 99%